Tetrasomy 8 in Haematological Malignancies-A Case Series - Neeraja Koppaka (JCDR Research and Publications Private Limited, 2021)
Tetrasomy 8, a rare genetic abnormality in haematological disorders is associated with Acute Myeloid Leukaemia (AML), Myelodysplastic Syndrome, Myeloproliferative Neoplasms and Acute Non Lymphocytic Leukaemia. It may be found as a sole chromosomal abnormality or coexist with Trisomy 8. Tetrasomy 8 has shown to have proliferative advantage and aggressive clinical course with lower survival rates. Four cases of Tetrasomy 8 were reported in present series, of which one case showed Tetrasomy 8 as a sole chromosomal abnormality, two cases with it’s coexistence with Trisomy 8 and one case with complex rearrangement of chromosome 8. Trisomy 8 as a sole abnormality is associated with intermediate prognosis; hence the aggressive behaviour of the disease with Tetrasomy 8 can be attributed to increase in gene dosage of extra chromosome 8. The fourth case of AML with monocytic differentiation showed complex karyotype with presence of two isochromosomes 8, resulting in five copies for long arm of chromosome 8. This demonstrates presence of crucial genes for leukemogenesis in 8q region. From various studies, it is evident that the role of Tetrasomy 8 in poor prognosis and role of associated genes in leukaemogenesis needs further investigation on molecular deregulation mechanisms with biologic and clinical consequences. Building up on rare abnormalities by this study would help in a better understanding of the disease with appropriate classification and ultimately can lead to an effective clinical management.